Alle origini dell’ingerenza umanitaria: le potenze europee e la questione armena alla fine del XIX secolo - Tonini, Alberto (Rivista di studi politici internazionali, 2007)
Based on diplomatic documents recently published by the Italian Ministry for Foreign Affairs, this essay presents the European powers’ policy concerning the Armenian question during the last decade of the XIXth century. Author’s attention is focused on the heavy massacres occurred in 1894-95 and on the European powers’ decision to set up an international commission to inquire into the massacres. Describing those events, however, he offers an insight about the state of relations between the Ottoman Empire and the European powers during the last part of the XIXth century. RÉSUMÉ - L’Auteur étudie la politique des puissances européennes par rapport à la question arménienne pendant la dernière partie du XIXème siècle. En particulier, il analyse les atroces massacres des années 1894-95 et la décision des puissances européennes de créer une commission internationale d’enquête pour identifier les responsables des crimes. En examinant les travaux de la commission à travers les ocuments diplomatiques du Ministère italien des Affaires Étrangères, l’Auteur donne un aperçu de l’état des relations entre l’Empire ottoman et les puissances européennes à l’époque